mecA and PVL genes in methicillin-resistant Staphylococcus aureus from clinical specimens: a cross-sectional hospital based study from Nepal - Sirjana Adhikari; Supriya Sharma; Sanjib Adhikari; Sanjit Shrestha; Dwij Raj Bhatta (Iranian Journal of Microbiology)
Background and Objectives: Staphylococcus aureus has increasingly been associated with community and healthcare-associated infections worldwide and contributes to treatment failures due to the emergence of multidrug-resistant (MDR) and methicillin-resistant Staphylococcus aureus (MRSA) strains. We aimed to determine the prevalence and antibiotic susceptibility pattern of MRSA isolated from patients attending a burn center and to detect mecA and PVL genes among MRSA isolates. Materials and Methods: A cross-sectional hospital based study was conducted on 1950 clinical samples collected from hospital inpatients and outpatients of Kirtipur Hospital, which is a burn specialist hospital in Kathmandu, Nepal. Each sample underwent conventional cultural methods for bacterial isolates identification. Results: Out of 1950 samples, 452 (23.2%) samples showed bacterial growth, of which 109 isolates (24.1%) were identified as Gram positive and 343 (75.9%) as Gram negative bacteria. Among the Gram positive bacteria, 53 (48.62%) were Staphylococcus aureus. Of the total S. aureus isolates, 40 (75.5%) were MRSA and 48 (90.6%) were MDR. Of the 40 MRSA isolates, 29 (72.5%) carried the mecA gene and 3 (7.5%) harbored PVL gene. Conclusion: The high prevalence of MRSA in a burn unit underscores the need for more rigorous infection control practices that follow standard protocols to reduce MRSA transmission in both individuals and the hospital environment.